Knowledge management : dependency, creation and loss in industrial history - Wilson, J. F.; Jones, Ian (Senior research assistant); Toms, Steven (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This shortform book presents key peer-reviewed research selected by expert series editors and contextualised by new analysis from each author on the subject of knowledge management in industrial history. With contributions on knowledge management, knowledge transfer, knowledge loss, knowledge creation, competition and co-operation in producing skilled employees, and ownership structures and their relation to knowledge management, this volume provides an array of fascinating insights into industrial history. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences"--
OCLC-licensed vendor bibliographic record.
Keywords: Knowledge management -- History; Industrial management -- History; Industries -- History; BUSINESS & ECONOMICS / Corporate & Business History; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Industries / Energy Industries